Role of Product Innovation and Market Orientation on Business Performance - Lasmy, Lasmy; Syahchari, Dicky Hida; Herlina, Maria Grace; Saroso, Hardijanto; Sudrajat, Darjat (International Journal of Supply Chain Management, 2020)
Micro Small Medium Enterprises (MSME) give the big impact and the main power of many countries include Indonesia. They contribution of Gross Domestic Product (GDP) is bigger than large companies, has a large market share and has a high labour absorption. That fact is a trigger for academics and professionals to conduct research on it, to get more information, understanding and look for what influences the MSME business performance. This study aims to analyse the role of product innovation and market orientation toward business performance of micro small enterprise in food and beverage sector in Jakarta. Data collected through questionnaire and filled by 390 owners of micro small enterprise in food and beverage sector in Jakarta. Meanwhile, for data analysis using Statistical Package for the Social Science (SPSS). This study is quantitative study. The results are both of product innovation and market orientation has a positive effect on business performance